Tailored surgical approaches for spinal chordomas: a multidisciplinary perspective - Klein, Lukas; Lenga, Pavlina; Dao Trong, Huy Philip; Kleineidam, Helena; Krieg, Sandro; Ishak, Basem (Acta neurochirurgica, 2024)
The treatment of spinal chordomas presents a significant challenge due to their resistance to both radiotherapy and chemotherapy as well as the complexity of the surgical procedures required. This study presents a series of cases of primary spinal chordomas, focusing on the development of a personalized therapeutic strategy that is tailored to each patient's unique clinical status. This approach aims to ensure that treatments are optimally aligned with the patient’s overall prognosis and surgical eligibility.
Gesehen am 10.04.2025